Ryszard Berwiński’s Studia o literaturze ludowej and Historiographical Concepts of the Early Slavic World in the Nineteenth Century - Raczyńska, Sabina (Literatura Ludowa. Journal of Folklore and Popular Culture, 2020)
The aim of the article is to show how, in his Studia o literaturze ludowej (Studies on folk literature), Ryszard Berwiński evaluated the nineteenth-century historiographical concepts of the Slavic world and ancestry. The first part of the article discusses Berwiński’s approach to the general theory of “folk element/energy”, whose influence manifested itself for example in discussions of the history of literature as divided into Slavic-Polish and Latin-Polish. The second part briefly introduces the nineteenth-century theories of the origin of the Polish nation and their assessment in contemporary research. The third part of the article presents how Ryszard Berwiński commented on those concepts, on the historiography of his time, and on the ideas about the early Slavic world.